2023
DOI: 10.1039/d3tc00452j
|View full text |Cite
|
Sign up to set email alerts
|

Origins of near-infrared-II emission tail and fluorescence enhancement of albumin-chaperoned cyanine dyes from a multiscale computational study

Abstract: Repurposing the commercially available NIR-I cyanine dyes for NIR-II imaging has attracted increasing research interest. The bright tail emission of present NIR-I dyes can afford high-performance NIR-II imaging with improved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Although the FRET-based quenching process is inherently inefficient due to the small spectral overlap of the excited fluorophore with the high energy of the O–H vibrational transitions, there is considerable additivity due to the high number of independent energy-accepting water molecules that are close to the dye surface. Recently reported molecular dynamics simulations suggest that a free heptamethine cyanine dye molecule in pure aqueous solution is surrounded by a surface solvation shell composed of 100 to 200 water molecules. , Moreover, binding of the dye by albumin protein reduces the average number of water molecules surrounding the dye by about a factor of 2 (Scheme ). Since FRET efficiency has a 1/ r 6 dependence on the distance r between the excited state fluorophore as the energy donor and nearby water molecule as the energy acceptor, the number of surface water molecules should determine the amount of fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the FRET-based quenching process is inherently inefficient due to the small spectral overlap of the excited fluorophore with the high energy of the O–H vibrational transitions, there is considerable additivity due to the high number of independent energy-accepting water molecules that are close to the dye surface. Recently reported molecular dynamics simulations suggest that a free heptamethine cyanine dye molecule in pure aqueous solution is surrounded by a surface solvation shell composed of 100 to 200 water molecules. , Moreover, binding of the dye by albumin protein reduces the average number of water molecules surrounding the dye by about a factor of 2 (Scheme ). Since FRET efficiency has a 1/ r 6 dependence on the distance r between the excited state fluorophore as the energy donor and nearby water molecule as the energy acceptor, the number of surface water molecules should determine the amount of fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Recently reported molecular dynamics simulations suggest that a free heptamethine cyanine dye molecule in pure aqueous solution is surrounded by a surface solvation shell composed of 100 to 200 water molecules. 36 , 38 Moreover, binding of the dye by albumin protein reduces the average number of water molecules surrounding the dye by about a factor of 2 ( Scheme 2 ). 38 Since FRET efficiency has a 1/ r 6 dependence on the distance r between the excited state fluorophore as the energy donor and nearby water molecule as the energy acceptor, the number of surface water molecules should determine the amount of fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6B and C). 35 However, unlike the traditional symmetry breaking caused by the large amplitude movement of molecules after the conjugated system is excited, the combination of dyes and albumin has a lesser effect on the conjugated scaffold, 88 such as IR-780@BSA with an absorption wavelength of 790 nm but the absorption wavelength of IR-780 is 775 nm. 38…”
Section: Site-specific Albumin Tagging With Cl-containing Near-infrar...mentioning
confidence: 99%
“…13,14 Recent studies have found that ICG has tailing fluorescence emission in the NIR-II and can provide higher tumor sensitivity during NIR-II imaging, which can further expand its application in the clinical field. 15–17 Carr et al successfully employed ICG for real-time imaging of NIR-II fluorescence, including non-invasive imaging of blood and lymphatic vessels in addition to hepatobiliary clearance, showing advantages such as greater contrast than NIR-I imaging. 18 However, ICG lacks specificity for tumors and has the disadvantage of being unstable in aqueous solution and prone to form H-dimer.…”
Section: Introductionmentioning
confidence: 99%